FHIR-to-Snowflake: Building Interoperable Healthcare Lakehouses Across State Exchanges - Jani, Parth (International Journal of Emerging Research in Engineering and Technology, 2025)
The combination of FHIR (Fast Healthcare Interoperability Resources) with Snowflake is investigated in this paper to build interoperable healthcare lakehouses enabling effective interchange of eligibility and encounter data between Third-Party Administrators (TPAs) and payers. Healthcare data interoperability still presents a significant obstacle across state exchanges as broken systems cause delays, inefficiencies, and higher costs by impeding seamless data flow. Using Snowflake's scalable data cloud platform and FHIR APIs, this solution offers secure, real-time data sharing enabling TPAs and payers to access and distribute critical patient data like eligibility status and encounter history. This approach reduces the complexity of several data systems and advances a compliant, coherent data environment following industry standards.  For healthcare players, this integration greatly increases operational efficiency, sharpens decision-making & reduces their expenses. Furthermore, it finally improves patient care by means of quick access to accurate more data, encouragement of transparency, & support of better informed clinical and also more financial decisions. Emphasizing the need of improving healthcare data interoperability for the advantage of all stakeholders in the healthcare ecosystem, the article outlines the transforming possibilities of combining Snowflake and FHIR APIs